Weighted Strong Law of Large Numbers for Random Variables Indexed by a Sector - Przemysław Matuła; Michał Seweryn (Journal of Probability and Statistics)
We find necessary and sufficient conditions for the weighted strong law of large numbers for independent random variables with multidimensional indices belonging to some sector.